Malondialdehyde (MDA) Serum Level In Incomplete Abortion Is Higher Than Normal Pregnancies - Putu Surya, I Gede (E-Journal Obstetric & Gynecology Udayana, 2013)
Miscarriageor spontaneous abortion is one of the most frequent obstetric complications encountered during the first trimester of pregnancies. More than 80% occur in less than 14 weeks of pregnancy. Clinically, the most common miscarriage in hospitals is incomplete abortion. On of the cause of miscarriage is oxidative stress due tounbalance between prooxidants (free radical) and antioxidants. Malondialdehyde (MDA) is compound which is the end product of lipid peroxidants in the body.MDA showedsaturated fatty acid oxidation products from free radicals. Increased free radicals will caused oxidative stress. An increase in oxidative stress in accordance with increased MDA formation. Oxidative stress will cause breakage and damage tothetrofoblast cells that continued to be miscarriage. The purpose of this research was to provethat the MDA levels in incomplete abortionishigher than normalpregnancies. The design on this research used a cross-sectional study involving 72 women, grouped into 36 women with incomplete abortions and 36 womenwith normal pregnancy less than 14 weeks which meet the criteria of inclusion and exclusion that came to the Sanglah HospitalDenpasar. Blood serum were checked to determine serum MDA levels in both groups byElisa method. Based on t-independent test, therewereno significance differences in terms of age mother, the age of pregnancy and the parity between groups were gestational age less than 14 weeks(p > 0.05). There were significant differences (p < 0.05) between MDA serum levels in incomplete abortion(2.50+ 1.38) andnormal pregnancy less than 14 weeks (1.78 + 0.38).From chi-square test, prevalence ratio is(RP = 1.98, IK 95 % = 1.20-3.26 p = 0.005). Based on ROC curve, cut off point of mda serum levels was1.836 pmol/mg. MDA serum level in incomplete abortion is higher thannormal pregnancies. Keyword : incomplete abortion, MDA serum level